Are Immigrants Competing with Natives in the Italian Labour Market? The Employment Effect - Alessandra Venturini; Claudia Villosio (Institute for the Study of Labor (IZA), 2002)
Gavosto, Venturini, Villosio (1999) find that the impact of foreign workers on the wage of natives was positive. Such a result was partly to be expected, and therefore the effect of immigrants on native employment is analyzed here. Two aspects of the unemployment experience are taken into account: i) displacement risk, measured by the probability of moving from employment into unemployment; ii) job-search effectiveness measured by the probability of moving from unemployment into employment within one year. The quarterly Labour Force Survey data (ISTAT) from 1993 to 1997 was used. The transition probabilities depend on two sets of independent variables at time t: the individual characteristics and the external conditions of the market. A probit model was applied for repeated-cross-sections on ?specific? local areas in order to control for possible autocorrelation and endogeneity. The results show that in the northern part of Italy, where most immigrants are located, the share of immigrants has no effect or a complementary effect on the probability of finding a job for workers looking for a new job while for people looking for a first job (the young) a negative effect is detected only in 1993 while the effect is positive in the most recent periods. For native transition from employment to unemployment a complementary effect prevails, while there is a negative effect only in the manufacturing sector in Northern Italy for 1996. This effect, however, is possibly due to other factors, i.e. the spread of temporary contracts in that area during that year.
Keywords: J61; F22; 330; migration; competition; employment; unemployment; Migranten; Ausländische Arbeitskräfte; Arbeitsmarkt; Wettbewerb; Arbeitslosigkeit; Schätzung; Italien